Factors that Affect the MSME Taxpayer Compliance with Education Level as the Moderating Variable - Hidayat, Affan; Akbar, Taufik (ARE Publisher, 2024)
Objectives: The objectives of this study is to obtain the empirical evidence about the effect of tax knowledge, tax penalties, e-filling on MSME taxpayer compliance with education level as a moderating variable at KPP Pratama Pondok Gede, Bekasi City. Methodology: The type of data used is primary data. The sample of this study were 100 MSME respondents at KPP Pratama Pondok Gede, Bekasi City who were registered. Data analysis using path analysis using the SmartPLS 4.0 application was used to test the hypothesis. Finding: The results of this study concluded that tax knowledge has a significant effect on taxpayer compliance, tax sanctions have no significant effect on taxpayer compliance, e-filling has no significant effect on taxpayer compliance. Conclusion: The level of education is not able to moderate tax knowledge on taxpayer compliance, the level of education is not able to moderate tax sanctions on taxpayer compliance, the level of education is not able to moderate e-filling on taxpayer compliance.